Pengobatan Tuberculosis Melalui Program DOTS di Puskesmas Kecamatan Pasar Rebo Jakarta Timur - Reni Mardiana Sutanti; Ricky Riyanto Iksan (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Tuberculosis is a chronic infectious disease that is still a public health problem. Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis which often attacks the lungs and other body organs. One strategy for controlling tuberculosis is to use Directly Observed Treatment Shortcourse (DOTS). Apart from that, family function also plays an important role in the process of successful tuberculosis treatment. Objective This research is to identify the relationship between family function and the results of tuberculosis treatment in adults with the DOTS program in the work area of ​​the Pasar Rebo District Health Center, East Jakarta. Research type this is a quantitative research with a cross sectional research design. Population in this study there were adults suffering from Tuberculosis in the working area of ​​the Pasar Rebo District Health Center, East Jakarta with a total of 123 people, while the number of respondents from this study was 55 people. Method data collection in this study used a questionnaire. Research results the affective function variable was found with a p-value of 0.015, the socialization function with a p-value of 0.007 and the family care function with a p-value of 0.000, there were no variables that had a p-value > 0.05. Conclusionfrom this research, there is a relationship between family function and the results of tuberculosis treatment in adults with the DOTS program in the working area of ​​the Pasar Rebo District Health Center, East Jakarta.